Proteína C reactiva como factor predictor en pacientes con apendicitis aguda perforada en el Hospital Víctor Lazarte Echegaray - Medina Briones, Michel (2022)
The acute inflammatory abdomen encompasses the main conditions seen by surgeons working in emergency services around the world. It is a clinical picture that ranges from simple, self-limited and benign diagnoses to those that threaten life and require rapid surgical intervention. Acute appendicitis (AA) represents the most frequently diagnosed surgical condition in the abdomen1, in this sense it is of interest to verify those variables that can predict the natural history of this disease, there is evidence that the increase in the levels of c-reactive protein it is associated with the severity of the disease and the risk of perforation of the cecal appendix; For this reason, it is intended to corroborate the relationship described in other populations, in order to recognize the usefulness of this analytical marker in the prediction of this outcome.